Apache Solr enterprise search server : enhance your searches with faceted navigation, result highlighting, relevancy-ranked sorting, and much more with this comprehensive guide to Apache Solr 4 - Smiley, David (Birmingham, UK : Packt Publishing, 2015)
This book is for developers who want to learn how to get the most out of Solr in their applications, whether you are new to the field, have used Solr but don't know everything, or simply want a good reference. It would be helpful to have some familiarity with basic programming concepts, but no prior experience is required.
Rolling back an uncommitted changeThe transaction log; Atomic updates and optimistic concurrency; Sending CSV-formatted data to Solr; Configuration options; The DataImportHandler framework; Configuring the DataImportHandler framework; The development console; Writing a DIH configuration file; Data sources; Entity processors; Fields and transformers; Example DIH configurations; Importing from databases; Importing XML from a file with XSLT; Importing multiple rich document files -- crawling; Importing commands; Delta imports; Indexing documents with Solr Cell.
Online resource; title from cover (Safari, viewed June 10, 2015).
Online resource; title from PDF title page (EBSCO, viewed July 10, 2017).
Includes index.
Includes bibliographical references and index.
Keywords: Search engines -- Programming; Web search engines; Apache (Computer file : Apache Group); Open source software; Application software -- Development; Database searching; Internet searching; Web search engines; COMPUTERS -- Web -- Search Engines; COMPUTERS -- Web -- Web Programming; COMPUTERS -- Programming -- Open Source; Apache (Computer file : Apache Group); Open source software; Search engines -- Programming; Web search engines; Electronic books